Cultivating Critical Thinking through Ecopedagogy–Project Based Learning: An Innovative Student Worksheets for Biology Lesson Planning Course - Tutik Fitri Wijayanti; Nita Nuraini (UIN Fatmawati Sukarno Bengkulu, 2026)
The increasing environmental issues, both locally and globally, demand that everyone possess high critical thinking skills. Without this ability, actions tend to be reactive and superficial, resulting in ineffective solutions and ongoing environmental problems. However, the fact remains that the critical thinking skills of students in Indonesia are still relatively low. This study aims to develop students worksheets on Ecopedagogy-Project Based Learning (Ecopedagogy-PjBL) to improve students’ critical thinking skills. The research method used is R&D with the ADDIE model. The research subjects are biology education students at Muhammadiyah University of Palembang. The results show that three validators declared the developed worksheets valid, received very positive student response, and significantly improved critical thinking skills. Therefore, the developed Ecopedagogy-PjBL, worksheets can enhance biology education students’ critical thinking skills.